The mad scientist's secret - Miller, Marvin; Tallarico, Tony; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1994)
The reader solves a variety of puzzles, riddles, mazes, and secret codes to help stop the Mad Scientist Dr. XXX from turning students into zombies with his secret formula for sludge which tastes just like school cafeteria food.
Keywords: Detective and mystery stories; Mystery and detective stories